Visual Deprivation Retards the Maturation of Dendritic Fields and Receptive Fields of Mouse Retinal Ganglion Cells - Chen, Hui; Xu, Hong-Ping; Wang, Ping; Tian, Ning (Frontiers in Cellular Neuroscience, 2021)
It was well documented that both the size of the dendritic field and receptive field of retinal ganglion cells (RGCs) are developmentally regulated in the mammalian retina, and visual stimulation is required for the maturation of the dendritic and receptive fields of mouse RGCs. However, it is not clear whether the developmental changes of the RGC receptive field correlate with the dendritic field and whether visual stimulation regulates the maturation of the dendritic field and receptive field of RGCs in a correlated manner. The present work demonstrated that both the dendritic and receptive fields of RGCs continuously develop after eye-opening. However, the average size of the receptive field increases more than that of the dendritic field, suggesting a continuous increase of synaptic converging of RGC synaptic inputs. Besides, light deprivation impairs both the developmental increase of dendritic and receptive fields.